Compartiendo - Abierto, Espacio (Espacio Abierto, 2021)
XVI Congreso Latinoamericano de medicina social y salud colectiva VII Encuentro Latinoamericano de Metodología de las Ciencias Sociales 21 de octubre al 27 de noviembre de 2021 ISA Award for Excellence in Research and Practice Nominations and all supporting documentation should be sent by email before May 30, 2021 to the ISA Secretariat isa@isa-sociology.org with copies to the Chair of the ISA Award Committee for Excellence in Research and Practice, Sari Hanafi, ISA President, sh41@aub.edu.lb. Diploma Superior Gestión, investigación y usos pedagógicos de archivos en la era digital